miR-141-3p Targeted SIRT1 to Inhibit Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells - Shuzuo Zhou; Gang Zhang; Kun Wang; Zhong Yang; Yinghui Tan (Hindawi Limited, 2023)
Purpose. To explore the expression of miR-141-3p during the osteogenic differentiation of human bone marrow mesenchymal stem cells (BMSCs) and its regulatory effect. Methods. Differentiation of BMSCs was induced by dexamethasone. The mRNA expression of miR-141-3p, ALP, RUNX2, and OCN was measured using RT-qPCR. The protein expression was detected via western blot. The target of miR-141-3p was predicted through the TargetScan website and confirmed using luciferase reporter assay. Results. miR-141-3p expression declined during osteogenic differentiation. The relative ALP activities and the mRNA expression of ALP, RUNX2, and OCN were markedly reduced in the miR-141-3p mimic group while increased in the inhibitor group. Cell viability was suppressed in the miR-141-3p mimic group and promoted in the inhibitor group. SIRT1 was predicted to be a downstream gene of miR-141-3p, and this prediction was confirmed via the luciferase reporter assay. The results of the western blot assay demonstrated that SIRT1 expression was decreased in the miR-141-3p mimic group. SIRT1 reversed the inhibitory influence of miR-141-3p on the osteogenic differentiation ability of BMSCs. Conclusion. miR-141-3p targeted SIRT1 to inhibit osteogenic differentiation of BMSCs via the Wnt/β-catenin signaling pathway.